Denosumab for the management of bone disease in patients with solid tumors. Issue 3 (March 2012) - Body, Jean-Jacques
Many patients with advanced cancer develop bone metastases, which reduces their quality of life. Bone metastases are associated with an increased risk of skeletal-related events, which can lead to increased morbidity and mortality. In patients with bone metastases, tumor cells disrupt the normal process of bone remodeling, leading to increased bone destruction. Denosumab is a fully human monoclonal antibody against receptor activator of NF-κκB ligand (RANKL), a key regulatory factor in bone remodeling. By binding to RANKL, denosumab disrupts the cycle of bone destruction. In clinical studies in patients with prostate or breast cancer and bone metastases, denosumab was superior to the current standard of care, zoledronic acid, for delaying skeletal-related events, while in patients with other solid tumors or multiple myeloma, denosumab was noninferior to zoledronic acid. This article examines the pharmacokinetics, efficacy, and safety and tolerability of denosumab for the management of bone events in patients with cancer.